Monetary policy and financial conditions: A cross-country study - Tobias Adrian; Fernando Duarte; Federico Grinberg; Tommaso Mancini Griffoli (Federal Reserve Bank of New York, 2019)
Loose financial conditions forecast high output growth and low output volatility up to six quarters into the future, generating time-varying downside risk to the output gap, which we measure by GDP-at-Risk (GaR). This finding is robust across countries, conditioning variables, and time periods. We study the implications for monetary policy in a reduced-form New Keynesian model with financial intermediaries that are subject to a Value at Risk (VaR) constraint. Optimal monetary policy depends on the magnitude of downside risk to GDP, as it impacts the consumption-savings decision via the Euler constraint, and financial conditions via the tightness of the VaR constraint. The optimal monetary policy rule exhibits a pronounced response to shifts in financial conditions for most countries in our sample. Welfare gains from taking financial conditions into account are shown to be sizable.
Keywords: E52; 330; monetary policy; financial conditions; financial stability